RECRYSTALLIZATION MECHANISMS OF FERGUSONITE FROM METAMICT MINERAL PRECURSORS - Tomašić N.; Bermanec V.; Gajović A.; Su D.S.; Schlögl R.; Rajić Linarić M.; Ntaflos T. (My University, 2006)
The metamict state and recrystallization of fergusonite in metamict natural samples were studied by thermal methods (TGA-DTA), X-ray powder diffraction (XRD), Raman spectroscopy (RS), transmission electron microscopy (TEM), selected area electron diffraction (SAED), and electron microprobe (EPMA). Two metamict mineral samples of fergusonite were investigated in order to identify the original premetamict crystal structure and to identify recrystallization mechanisms. The TEM data and RS provided evidence on the partial preservation of the original structure in the investigated minerals, which are X-ray amorphous. It was shown that fergusonite could recrystallize from a metamict mineral with original fergusonite structure or from metamictized pyrochlore, which was altered before or after metamictization. Two recrystallization mechanisms were recognized: (a) epitaxial growth occurring at the boundary between preserved premetamict structure fragments and completely metamictized areas, and (b) nucleation-crystal growth mechanism occurring in completely amorphous areas of the minerals, and resulting in recrystallization of the original mineral as well as in the crystallization of a new mineral with a modified chemical composition as compared to the initial matrix. © Springer-Verlag 2006.
Keywords: FERGUSONITE; METAMICT STATE; RAMAN SPECTROSCOPY; RECRYSTALLIZATION MECHANISMS; TEM